Pre-sleep heart rate variability predicts chronic insomnia and measures of sleep continuity in national-level athletes - Li, Q.; Lei, X.; Yu, W.; Steward, C. J.; Zhou, Y. (Frontiers in Physiology, 2025)
Objective: This study aimed to investigate whether pre-sleep heart rate variability (HRV) could predict chronic insomnia (CI) and sleep quality in male national-level team-based athletes.